Dihydroartemisinin is an inhibitor of ovarian cancer cell growth - Jiao Yang; Ge Chun-min; Meng Qing-hui; Cao Jian-ping; Tong Jian; Fan Sai-jun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the anticancer activity of dihydroartemisinin (DHA), a derivative of antimalaria drug artemisinin in a panel of human ovarian cancer cell lines. Methods: Cell growth was determined by the MTT viability assay. Apoptosis and cell cycle progression were evaluated by a DNA fragmentation gel electro-phoresis, flow cytometry assay, and TUNEL assay; protein and mRNA expression were analyzed by Western blotting and RT-PCR assay. Results: Artemisinin and its derivatives, including artesunate, arteether, artemether, arteannuin, and DHA, exhibit anticancer growth activities in human ovarian cancer cells. Among them, DHA is the most effective in inhibiting cell growth. Ovarian cancer cell lines are more sensitive (5-10-fold) to DHA treatment compared to normal ovarian cell lines. DHA at micromolar dose levels exhibits a dose- and time-dependent cytotoxicity in ovarian cancer cell lines. Furthermore, DHA induced apoptosis and G2 cell cycle arrest, accompanied by a decrease of Bcl-XL and Bcl-2 and an increase of Bax and Bad. Conclusion: The promising results show for the first time that DHA inhibits the growth of human ovarian cancer cells. The selective inhibition of ovarian cancer cell growth, apoptosis induction, and G2 arrest provide in vitro evidence for further studies of DHA as a possible anticancer drug in the clinical treatment of ovarian cancer.